Preference Analysis and Purchasing Decision of Fruit Consumers in Generation Y (Case of Modern and Traditional Retail in Bogor) - Effendi, Irpan; Najib, Mukhamad; Brandoko, Kir (Department of Family and Consumer Sciences, Faculty of Human Ecology, IPB University, 2019)
Fruit is categorized as perishable product. Fruit trading still coordinated by direct sales, which consumers come over to the location then choose their own preference. Majority consumers prefer to go to the two shopping places for buying fruit products which is major in Indonesia or Bogor, for instance in modern retail or traditional retail. The issue in consumption character shifts caused by the generation alteration in which can influence business activities in the retail industry. At present, the traditional good retailers of modern generation Y is faced with different characteristics from the previous generation. Data was collected using questionnaires given to 150 respondents from the modern retail and 150 respondents traditional retail. The total questionnaires are 300 Generation Y respondents. The data was analyzed by descriptive analysis and Partial Least Square (PLS). The results indicated that the category in the modern retail the influence of the reference group and ethnocentrism had a positive effect and had the greatest influence on Y generation preferences as well as the categories in traditional retail reference groups and ethnocentrism had a positive and significant effect and product quality and prices have a negative effect on Y generation's preference for fruit shopping in modern retail. Meanwhile personal factors and places have a negative effect on Y generation's preference for fruit shopping in traditional retail. From modern and traditional fruit retailing consumer preferences have a positive and very significant effect on fruit purchasing decisions.